Urban remote sensing with lidar for the Smart City Concept implementation - Kostrikov, Sergiy Vasylovych (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2019)
Introduction of the problem. The paper emphasizes that the key features of the contemporary urban development have caused a number of challengers, which require the innovative technological introductions in urban studies. The research goal of this paper means representing a multifunctional approach, which combines author’s urbogeosystem (UGS) theory with the URS (Urban Remote Sensing) technique for LiDAR (Light Detection And Ranging) data processing. The key elements of the Smart City concept within a geospatial perspective. Three basic assumptions are implied due to the affiliation “a geospatial perspective ó the Smart City concept” (SCC). The five key elements of the SCC have been outlined: Innovations; Scalability; Data gathering, measuring, and mining; Addressing environmental challengers; Interlink between the smart meter information and the geo-sensor information. The urbogeosystemic approach as a tool for simulating the “smart urban environment” – a core node of the Smart City hierarchy. The urbogeosystemic ontological model has been introduced as a trinity-tripod (urban citizens, municipal infrastructure, urbanistic processes and phenomena). The “smart urban environment” is a core node of an urbogeosystem. Processing results of LiDAR surveying technique. With increasing availability of LiDAR data, 3D city models of robust topology and correct geometry have become the most prominent features of the urban environment. Three key advantages of the LiDAR surveying technique have been introduced. The flowchart of the operational URS / LiDAR / GIS workflow for the Smart City implementation has been depicted. Urban Remote Sensing for data mining / city analytics and the EOS LiDAR Tool. ELiT (EOS LiDAR Tool) software is both a separate web-based (network) generator (an engine) – ELiT Server, and an integrated component of EOS Platform-as-a-Service software – ELiT Cloud. The allied one to these two products is our desktop ElitCore software, that possesses even broader functionality. The paper outlines the whole framework of urban data mining / city analytics relevant to the mentioned applications. The ELiT software use cases for the Smart Cities. A number of use cases that can be completed with the ELiT software in the common urban planning domain have been described and illustrated. Each from five scenarios presented suggests some unique solution within the frameworks of the SCC implementation. Conclusion, future research and developments. The completed research results have been summarized. An entity of the urban geoinformation space has been introduced. A geodatabase of ELiT 3D city models has been assigned a mandatory key component of the urban decision support system.